The Rise of Digital Finance in the COVID-19 Crisis: Bitcoin in E-Commerce, Insurance Fraud Mitigation, and Portfolio Optimization - Rostami, Leyla (International Journal of Business Management and Entrepreneurship, 2025)
The COVID-19 pandemic has significantly accelerated the adoption and evolution of digital finance, reshaping key financial sectors globally. This study investigates three critical areas impacted by the crisis: Bitcoin’s growing role in e-commerce, the application of machine learning for insurance fraud detection, and portfolio optimization strategies under volatile market conditions. Bitcoin exhibited unprecedented volatility during the pandemic, yet demonstrated a strong recovery trend, reflecting its increasing acceptance as both a speculative asset and a payment method. Insurance fraud detection models leveraging Random Forest algorithms achieved high accuracy and recall, highlighting the potential of artificial intelligence in mitigating financial risks amid rising fraudulent claims. Portfolio optimization using the Markowitz mean-variance framework revealed that strategic asset allocation can yield robust risk-adjusted returns despite market turbulence. These findings underscore the transformative effect of the COVID-19 crisis on digital finance, emphasizing the need for continued innovation, regulatory oversight, and ethical deployment of AI technologies. This study contributes to understanding how digital finance tools can enhance resilience and efficiency in uncertain economic environments.